Strengthening the Competitiveness of Indonesia’s Loser Sector Products in RCEP Cooperation - Abdullah, Ragimun; Rosjadi, Imran (Journal of Economics and Behavioral Studies, 2021)
The purpose of this study is to map some of Indonesia’s loser sector products which are commodities that need to be strengthened in the RCEP cooperation forum. In this study, the Revealed Comparative Advantage (RCA) formula is used to analyze the competitiveness of Indonesian export products. The average RCA results between, 2015-2019 show that out of the five food and beverage product items, most of them have high competitiveness. Meanwhile, the average RCA of livestock products, light industry and heavy industrial products has low competitiveness. A strengthening strategy to increase product competitiveness in the RCEP market requires several steps. These steps include identifying market access in RCEP partner countries, improving product quality and specialization, coordinating between the Government and the private sector and continuing to encourage bureaucratic reform, harmonization of regulations to obtain Smart Regulations.